The book of hope : a survival guide for trying times - Goodall, Jane, 1934-; Abrams, Douglas Carlton; Hudson, Gail E. (Celadon Books, 2021)
Jane Goodall and Douglas Abrams explore through intimate and thought-provoking dialogue one of the most sought after and least understood elements of human nature: hope. Drawing on decades of work that has helped expand our understanding of what it means to be human and what we all need to do to help build a better world, the book touches on vital questions, including: How do we stay hopeful when everything seems hopeless? How do we cultivate hope in our children? What is the relationship between hope and action? While discussing the experiences that shaped her discoveries and beliefs, Jane tells the story of how she became a messenger of hope, from living through World War II to her years in Gombe to realizing she had to leave the forest to travel the world in her role as an advocate for environmental justice. And for the first time, she shares her profound revelations about her next, and perhaps final, adventure.